EVALUATING THE IMPACT OF FINANCIAL MANAGEMENT PRACTICES ON ORGANIZATIONAL PERFORMANCE: A COMPARATIVE STUDY OF PUBLIC AND PRIVATE SECTOR COMPANIES - Dudang Gojali; Kadar Nurjaman; Muhammad Zaky; Iman Supratman (UIN Sunan Gunung Djati Bandung, 2024)
This study investigates the impact of financial management practices on organizational performance, focusing on a comparative analysis between public and private sector companies. Utilizing a comprehensive literature review and empirical data from financial reports, surveys, and interviews, the research identifies key financial management practices and assesses their effectiveness in enhancing organizational performance. The study highlights significant differences in the application and outcomes of financial management practices between the two sectors. In the public sector, stringent regulatory requirements and budgetary constraints often limit the flexibility of financial management, affecting performance outcomes. Conversely, private sector companies benefit from more adaptive financial strategies that drive efficiency and profitability. The findings indicate that while both sectors prioritize financial management, the methods and results vary substantially, impacting overall organizational success. This research contributes to the understanding of how tailored financial management practices can optimize performance across different organizational contexts. The study offers practical recommendations for managers and policymakers to improve financial management strategies, ultimately enhancing organizational effectiveness and sustainability.